2021
DOI: 10.31933/dijdbm.v2i2.651
|View full text |Cite
|
Sign up to set email alerts
|

Model Perceived Risk and Trust: E-Wom and Purchase Intention (The Role of Trust Mediating in Online Shopping in Shopee Indonesia)

Abstract: Purpose. This study discusses the Role of Trust in Mediating eWOM and Perceived Risk of Online Purchase Intention in Shopee. Design / methodology / approach. This study was conducted in Jakarta using 185 samples using SEM-PLS data analysis method. Findings. Trust is able to act as mediating between ewom and also perceived risk of online purchase intention in shopee. Practical implication. Shopee companies should be able to provide reliability in services and various features, and also increase security when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 32 publications
2
50
0
17
Order By: Relevance
“…As a result, they become more willing to purchase through such a medium. This study discovered that trust has a significant mediating effect on the relationship between perceived risk and online purchase intention (p = 0.000), which is consistent with the finding reported by Ilhamalimy and Ali (2021) in the context of online purchase intention in Shopee. Therefore, if consumers trust the online vendors or websites, it is less likely that they will experience negative outcomes but are more likely to purchase online.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As a result, they become more willing to purchase through such a medium. This study discovered that trust has a significant mediating effect on the relationship between perceived risk and online purchase intention (p = 0.000), which is consistent with the finding reported by Ilhamalimy and Ali (2021) in the context of online purchase intention in Shopee. Therefore, if consumers trust the online vendors or websites, it is less likely that they will experience negative outcomes but are more likely to purchase online.…”
Section: Discussionsupporting
confidence: 89%
“…In this sense, perceived risk is thought to be a predictor of trust (Hong & Cha, 2013) and past studies have evidenced that trust is a strong predictor of online purchase intention (Lowry et al, 2008;Maia et al, 2019). Besides, a recent study by Ilhamalimy and Ali (2021) has also found that trust has a mediating effect on the relationship between perceived risk and online purchase intention. Therefore, determining the potentialities and limits of online shopping requires a thorough understanding of trust (Clemons et al, 2016).…”
Section: Mediating Role Of Trust Between Perceived Risk and Online Pu...mentioning
confidence: 97%
“…Kepercayaan pelanggan juga menjadi faktor utama bagi pelanggan untuk memutuskan apakah akan membeli produk dari toko online atau tidak [29], [30], [33], [39]. Menurut [16], [28], [46], kepercayaan dapat dilihat sebagai keyakinan, sentimen, atau harapan tentang niat pembeli.…”
Section: Tabel 4 Structural Relationship Test Resultsunclassified
“…Purchasing decisions have been widely studied by previous researchers, including: (Maharani & Saputra, 2021), (Chauhan & Hudaya, 2020), (Al Hafizi & Ali, 2021), (Bimaruci et al, 2020), (F. Saputra & Mahaputra, 2022c), (Ilhamalimy & Ali, 2021), (F. Saputra & Mahaputra, 2022a).…”
Section: Literature Review Purchase Decisionsmentioning
confidence: 99%